Theologies of Enhancement? Another Look at Oliver O'Donovan's Created Order - Berkman, John (Toronto journal of theology, 2015)
In this response to Gerald McKenny's "Evolution, Biotechnology, and the Normative Significance of Created Order," John Berkman and Michael Buttrey suggest that McKenny has not adequately substantiated his claim that O'Donovan's account of "created order" provides no objection in principle to genetically "enhancing" children. Berkman and Buttrey frame an alternative reading of O'Donovan in light of O'Donovan's emphasis on "ordered love" as the task of Christian ethics, and his resolutely Trinitarian theology of created order. Contending contra McKenny that created order inheres in human persons and not only human nature abstractly understood, Berkman and Buttrey argue that for O'Donovan an ineliminable aspect of ordered love of God and neighbour is respecting the primordial teleological order of human persons, especially parents' rightly ordered love of the children entrusted to their care. In summary, Berkman and Buttrey conclude that unless McKenny puts O'Donovan's account of created order in its Trinitarian context and connects it with O'Donovan's rich account of ordered love, McKenny cannot make his case that O'Donovan's account of created order raises no inherent moral objection to genetically enhancing our children.